Neural stem cell assays - Kaur, Navjot; Vemuri, Mohan C. (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
"Including an overview of progress made in the field over the past decade, Neural Stem Cell Assays provides a detailed and comprehensive review of the basic methods for neural stem cell cultures. This one-stop reference for consistent methods and reliable tools spans the entire assay work flow, from isolation or generation of neural stem cells to characterization, manipulation and final application of NSCs in disease paradigms, such as Parkinson's disease, multiple sclerosis, and ALS. This is an excellent source of information for academic, pharmaceutic and biotechnology researchers"--Provided by publisher.
Machine generated contents note: 1. Neural Differentiation of Pluripotent Stem Cells / Mohan C. Vemuri. 2. The History and Design of Assays for the Identification, Characterization of Neural Stem Cells / Sharon A. Louis and Brent A. Reynolds. 3. Culture of Human Neural Stem Cells / Soojung Shin, Yiping Yan, and Mohan C. Vemuri. 4. GMP-compatible Production and Expansion of Human Neural Stem Cells / David J. Brick, Alexander E. Stover, Hubert E. Nethercott, Maria G. Banuelos, and Philip H. Schwartz. 5. Primary Rat Neural Cultures / Navjot Kaur. 6. Cryopreservation of Human Neural Stem and Progenitor Cells / Profico D., Sgaravizzi G., Projetti Pensi M., Muzi G., Ricciolini C., Gelati M., and Vescovi A.L. 7. Cryopreservation and Recovery of Primary Rat Neural Cells / Rhonda Newman and Navjot Kaur. 8. Efficient Induction and Scale up Generation of Neural Stem Cells from Human Pluripotent Stem Cells / Yiping Yan, Soojung Shin, and Mohan C. Vemuri. 9. Directed differentiation of Human NSC/NPC into Dopaminergic Neurons / Andrzej Swistowski and Xianmin Zeng. 10. In vitro Differentiation of Pluripotent Stem Cells towards either Forebrain GABAergic or Midbrain Dopaminergic Neurons / Brigham J Hartley, Bradley Watmuff, Cameron PJ Hunt, John M Haynes, and Colin W Pouton. 11. Generation of Astrocytes from Human Pluripotent Stem Cells using a Defined System / Atossa Shaltouki and Xianmin Zeng. 12. Directed differentiation of human PSC into Oligodendrocytes / Anu Hyysalo and Susanna Narkilahti. 13. Directed differentiation towards neural retinal cells / Deepak A. Lamba. 14. Directed differentiation of Photoreceptors and Retinal Pigment Epithelium from adult Mouse Retinal Stem Cells / Brian G. Ballios, Valeria Marigo, and Derek van der Kooy. 15. Induction of Schwann cells from bone marrow mesenchymal stem cells / Shohei Wakao, Masaaki Kitada, and Mari Dezawa. 16. Neural Cell Viability Assays / Bonnie J. Hanson and Michael K. Hancock. 17. Genetic modification of pluripotent stem cell derived human neural progenitor cells / Jamie M. Chilton and Steven L. Stice. 18. Electrophysiology of Neurons / Christine M. Wroge and Steven Mennerick. 19. Induction and transplantation of Neural Stem Cells from Human Pluripotent Stem Cells in Experimental Models (rat) of Parkinson's Disease / Makoto Motono, Asuka Morizane, and Jun Takahashi. 20. Transplantation of neural stem cells and progenitors in animal models of disease / Joseph F. Bonner and Itzhak Fischer. 21. Morphometric Assays for Neural Differentiation and Synaptic Development of Human iPSC-Derived NSC / Barbara Calabrese, Leif Dehmelt, and Shelley Halpain. 22. BacMam Transduction of Neural Stem Cells / Rene Quintanilla and Uma Lakshmipathy. 23. The Proximity Ligation Assay: A High Throughput Technique for Protein Analysis in Neuroscience / Michela Zaltieri, PierFranco Spano, Cristina Missale, and Arianna Bellucci. 24. Quantitation of micro-RNA expression in neural stem cells using TaqMan assays / Xavier Nissan and Alexandra Benchoua. 25. Genetic reporter cell lines: Tools for stem cell biology and drug discovery / Cameron PJ Hunt, Bradley Watmuff, Brigham J Hartley, Colin W Pouton, and John M Haynes.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Neural networks (Neurobiology); Electronic books